2019
DOI: 10.1534/genetics.119.301506
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans Transgenic Toolbox

Abstract: The power of any genetic model organism is, in part, derived from the ease with which gene expression can be manipulated. The short generation time and invariant developmental lineage have made Caenorhabditis elegans very useful for understanding, e.g., developmental programs, basic cell biology, neurobiology, and aging. Over the last decade, the C. elegans transgenic toolbox has expanded considerably with the addition of a variety of methods to control expression and modify genes with unprecedented resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 272 publications
0
107
0
1
Order By: Relevance
“…Similarly, researchers should also be aware that the tissue-specific promotors may also exhibit a low level of expression in other tissues, as was observed in this study (Radetskaya et al 2019). Transgenic approaches manipulating CRISPR-Cas9 activity in a tissue-specific manner (Shen et al 2014) or using conditional protein degradation methods may be more precise approaches for tissue-specific knockdown experiments in C. elegans (Nance and Frokjaer-Jensen 2019).…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, researchers should also be aware that the tissue-specific promotors may also exhibit a low level of expression in other tissues, as was observed in this study (Radetskaya et al 2019). Transgenic approaches manipulating CRISPR-Cas9 activity in a tissue-specific manner (Shen et al 2014) or using conditional protein degradation methods may be more precise approaches for tissue-specific knockdown experiments in C. elegans (Nance and Frokjaer-Jensen 2019).…”
Section: Discussionmentioning
confidence: 66%
“…Plasmids were co-injected at concentration 17 ng/μL with marker pHS4 (lin-48pro::mRFP) at concentration 50 ng/μL. Integrated transgenes were generated using TMP/UV as described (Nance & Frøkjaer-Jensen, 2019) and plasmids generated for this study can be found in Table S2.…”
Section: Let-653 Transgenesmentioning
confidence: 99%
“…These methods have enabled important discoveries but can also lead to artifacts due to supraphysiological gene-expression levels and lack of endogenous regulatory control. In recent years, the repertoire of C. elegans transgenic tools has expanded [see (Nance and Frøkjaer-Jensen 2019) for review], particularly due to advances in CRISPR/Cas9 genome-editing technologies (Paix et al 2014;Dickinson and Goldstein 2016). CRISPR/Cas9 allows precise transgene insertion by homology-directed repair (HDR) and can be used to label an endogenous gene at its native locus with a fluorescent protein (Dokshin et al 2018;Farboud et al 2019;Vicencio et al 2019).…”
Section: Introductionmentioning
confidence: 99%